Target gene screening and validation for RNAi-based suppression of the microsporidian parasite Vairimorpha (=Nosema) ceranae in honeybees - Sooho Lim; Hyeonha Yoo; Giyoun Han; Woojin Kim; Minlee Kim (Chemical and Biological Technologies in Agriculture)
Abstract The microsporidian Vairimorpha (=Nosema) ceranae is a major pathogen affecting honeybee health worldwide, yet safe and effective control strategies remain elusive. RNA interference (RNAi) using double-stranded RNA (dsRNA) has emerged as a promising strategy for species-specific suppression with minimal environmental impact, but effective target selection and mechanistic validation remain key challenges. Here, we screened 11 dsRNAs targeting V. ceranae genes and identified three potent targets (swp25, metap2, and spp). Among them, dsRNA-swp25 exhibited the most pronounced suppression efficacy, outperforming previously validated targets. qRT-PCR analysis confirmed significant post-transcriptional gene silencing, while spore load and midgut infection area were markedly reduced in bees treated with dsRNA-swp25. Furthermore, fluorescence imaging demonstrated that Cy3-labeled dsRNA was directly internalized by V. ceranae spores in a time-dependent manner without host mediation. Collectively, these findings highlight swp25 as a high-impact RNAi target and offer mechanistic insights into pathogen-directed RNAi responsiveness. This work advances the development of practical, environmentally sustainable RNAi-based strategies for apicultural disease management. Graphical Abstract